2019
DOI: 10.1002/hep.30204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of Cardiomyopathy in Children With Biliary Atresia Requiring Liver Transplantation

Abstract: BA-CCM is highly sensitive and specific for morbidity and mortality in children with BA listed for LT. 2DE screening for BA-CCM may provide pertinent clinical information for prioritization and optimal peri-transplant management of these children. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 40 publications
(108 reference statements)
0
41
1
1
Order By: Relevance
“…They concluded that CCM‐associated cardiac changes in pediatric patients with cirrhotic liver disease are frequent, mild, associated with cholestasis, and reversible after LT but may impact peritransplant care and posttransplant hospitalization time. This finding is in contrast to the study by Gorgis et al who documented an increased morbidity and mortality in children with CCM …”
Section: Chronic Liver Disease Leading To Cardiac Diseasecontrasting
confidence: 99%
See 3 more Smart Citations
“…They concluded that CCM‐associated cardiac changes in pediatric patients with cirrhotic liver disease are frequent, mild, associated with cholestasis, and reversible after LT but may impact peritransplant care and posttransplant hospitalization time. This finding is in contrast to the study by Gorgis et al who documented an increased morbidity and mortality in children with CCM …”
Section: Chronic Liver Disease Leading To Cardiac Diseasecontrasting
confidence: 99%
“…In addition to congenital cardiac disease, recent studies have suggested that up to 70% of patients with BA awaiting LT may develop cirrhotic cardiomyopathy (CCM) with an increased left ventricular mass index (LVMI), hyperdynamic contractility, and thickened left ventricular free wall and septum . The severity of LVMI was predictive of pretransplant, peritransplant, and posttransplant outcomes, with a high incidence of morbidity and mortality.…”
Section: Chd and The Livermentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of improved organ availability through increased deceased and live donation, new objective parameters for the PELD scoring system for infants are urgently needed. In their paper “Clinical consequences of cardiomyopathy in children with biliary atresia requiring liver transplantation,” Gorgis et al present a likely candidate for risk stratification . Cirrhotic cardiomyopathy (CCM) is characterized in adults by cardiac dysfunction (systolic and/or diastolic), left ventricular hypertrophy, and/or prolonged QT interval corrected for the heart rate .…”
mentioning
confidence: 99%